Investigation of Wear Behavior of Electroless Ni-P-W Coating under Dry and Lubricated Conditions Using RSM and Fuzzy Logic - Mukhopadhyay,Arkadeb (2016)
The present work aims to investigate and correlate the wear behavior of electroless Ni- P-W coating under dry and lubricated conditions with the tribological testing parameters. A pin -on -disc configuration test setup is used for the same. Taguchi's orthogonal design of experiments technique is used to carry out the experiments. Both response surface and fuzzy rule based models are seen to be effective in determining the complex interrelationship between the wear depth of the coatings and the test parameters, namely applied normal load, sliding speed and sliding duration. The coefficient of determination for fuzzy logic based predictions is seen to be higher than the regression predicted ones, indicating better modeling capabilities of the artificial intelligence technique. ANOVA results reveal that the wear depth is mostly influenced by sliding speed followed by applied normal load and sliding duration for both dry and lubricated conditions. Coating composition, phase transformation and microstructure studies are undertaken to analyze their effects on the wear behavior. Abrasive wear mechanism is seen to be the predominating under both dry and lubricated condition. The coatings are seen to suffer more wear under dry sliding condition compared to lubricated environment.